2016
DOI: 10.1007/s11606-016-3769-0
|View full text |Cite
|
Sign up to set email alerts
|

Anti-MDA5-Positive Dermatomyositis Presenting as Fever of Unknown Origin

Abstract: Dermatomyositis is a chronic systemic autoimmune disease characterized by inflammatory infiltrates in the skin and muscle. The wide variability in clinical and serologic presentation poses a diagnostic challenge for the internist. Appreciation of the clinical variants of dermatomyositis allows for expedient diagnosis and avoidance of diagnostic error. We illustrate these challenges with the case of a 51-year-old VietnameseAmerican man who initially presented with fever of unknown origin in the absence of overt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…The anti-MDA5 autoantibody JIIM phenotype was also associated with a high frequency of constitutional symptoms (weight loss, fever and adenopathy), as previously reported [15,16,31]. Fever has been described in 25-67% of anti-MDA5 JDM and DM patients, and furthermore, as a single presenting symptom in the absence of cutaneous or muscular manifestations of DM [32].…”
Section: Discussionsupporting
confidence: 76%
“…The anti-MDA5 autoantibody JIIM phenotype was also associated with a high frequency of constitutional symptoms (weight loss, fever and adenopathy), as previously reported [15,16,31]. Fever has been described in 25-67% of anti-MDA5 JDM and DM patients, and furthermore, as a single presenting symptom in the absence of cutaneous or muscular manifestations of DM [32].…”
Section: Discussionsupporting
confidence: 76%
“…Dermatomyositis is a rare cause of FUO in the literature that was found in our study. Lee et al [ 26 ] have reported a similar case presenting as FUO. They concluded that certain subtypes of dermatomyositis can present with atypical presentations as FUO.…”
Section: Discussionmentioning
confidence: 97%
“…The anti-Jo-1 antibody (anti-histidyl-tRNA synthetase), which is also classified as a myositis specific autoantibody, is the first antibody that was identified among various anti-ARS antibodies in ASA; anti-ARS antibodies are reported be detected in 20–40% of patients with IIM [ 23 , 24 ]. In the current study, 67 (77.9%) patients were tested for the anti-Jo-1 antibody, and 29.9% of the patients showed anti-Jo-1 positivity, which is in line with previous estimates [ 25 ].…”
Section: Discussionmentioning
confidence: 99%